2004
DOI: 10.1089/0889222041217374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Virological and Metabolic Effects of Switching Protease Inhibitor Combination Antiretroviral Therapy to Nevirapine-Based Therapy for the Treatment of HIV Infection

Abstract: Bordenave, B. Regions Hospital; Klebert, Michael; and Powderly, William G., ,"Evaluation of the virological and metabolic effects of switching protease inhibitor combination antiretroviral therapy to nevirapine-based therapy for the treatment of HIV infection." AIDS Research and Human Retroviruses.20,6. 589-594. (2004 ABSTRACTIn spite of indisputable benefits, the use of antiretroviral therapy is associated with multiple metabolic complications. Switching to simpler regimens might maintain viral suppression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Efavirenz, nevirapine, raltegravir, tenofovir, abacavir, and lamivudine have been associated with lower risk of mitochondrial toxicity, and low DM risk (44,45,46). In addition, newer PI, especially atazanavir and darunavir, have been shown to have lower metabolic toxicity and to rarely cause IR (47,48,49,50,51), a fact that could even explain the improvement of IR in pretreated patients switching to these drugs, as previously described with atazanavir, efavirenz, or nevirapine (47,52). However, the cross-sectional inclusion of our patients precludes us to know whether lower IR found in pretreated patients is due to persistence of this complication or is the result of progressive decrease with the use of new drugs with a lower toxicity.…”
Section: European Journal Of Endocrinologymentioning
confidence: 72%
“…Efavirenz, nevirapine, raltegravir, tenofovir, abacavir, and lamivudine have been associated with lower risk of mitochondrial toxicity, and low DM risk (44,45,46). In addition, newer PI, especially atazanavir and darunavir, have been shown to have lower metabolic toxicity and to rarely cause IR (47,48,49,50,51), a fact that could even explain the improvement of IR in pretreated patients switching to these drugs, as previously described with atazanavir, efavirenz, or nevirapine (47,52). However, the cross-sectional inclusion of our patients precludes us to know whether lower IR found in pretreated patients is due to persistence of this complication or is the result of progressive decrease with the use of new drugs with a lower toxicity.…”
Section: European Journal Of Endocrinologymentioning
confidence: 72%
“…Samples were selected from 19 patients who were part of a clinical trial in which patients with undetectable viral load on a stable protease inhibitor regimen continued that regimen for 6 months or switched the protease inhibitor to nevirapine. Details of these studies have been published elsewhere (19 ). This group allowed us to evaluate the changes over time of mtDNA in a variety of antiretroviral regimens and the effects of substituting the protease inhibitor for nevirapine, maintaining the nucleoside analog part of the regimen.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…Some studies demonstrated accelerated bone loss, while others showed stable or even increased BMD over time. [7][8][9] A meta-analysis reported that in studies that involved treatment-naive or untreated persons at baseline, BMD significantly declined at 1, 2, and 2.5 years after cART initiation. Conversely, in cohorts that involved cART-treated persons at baseline, BMD was stable over time.…”
mentioning
confidence: 99%